Dragonflies and damselflies of the West - Paulson, Dennis R. (Princeton field guides., 2009)
Dragonflies and Damselflies of the West is the first fully illustrated field guide to all 348 species of dragonflies and damselflies in western North America. Dragonflies and damselflies are large, stunningly beautiful insects, as readily observable as birds and butterflies. This unique guide makes identifying them easy--its compact size and user-friendly design make it the only guide you need in the field. Every species is generously illustrated with full-color photographs and a distribution map, and structural features are illustrated where they aid in-hand identification. Detailed species a.